Vision-based approach for the localisation and manipulation of ground-based crop. (30th July 2014) - Kadmiry, Bourhane; Wong, Chee Kit; Lim, Patrick P.K.
This article describes an approach to autonomous robotic farming based on vision and manipulation. The coherent technological setup is aiming at rendering intelligent crop manipulation based on crop localisation. The scientific contribution is focused on an approach that analyses point cloud information from a time-of-flight (ToF) camera to identify the location of foremost spring onions along the crop bed, for the intention of robotic manipulation. The process uses a combination of 2D image processing on the amplitude data, as well as depth analysis on the point cloud information, extracted from the camera to locate the desired object. Whilst the experimental results demonstrated the robustness of this approach, further testing is required to determine the ability of system to cope with different scenarios that exists in the naturally varying environment. Finally, the accuracy of the system has been validated in the physical world, to a certain extent, by integrating the localisation algorithm to the robotic manipulation system.